THE ROLE OF GENDER DIFFERENCES IN E-MEDIA USAGE, PHYSICAL ACTIVITY RATE AND NUTRITIONAL STATUS: AN INNOVATIVE SOCIAL MARKETING TOOL FOR HEALTH PROMOTION - Sarfo, Jacob Owusu; Bamfo, Emmanuel Appah; Asiedu, Michael; Adjei, Daniel (European Scientific Journal, ESJ, 2013)
The aim of this study is to use the social marketing approach to define the time spent on e-media and its effect on the pattern of exercise rate and nutritional status. Using a cross-sectional survey method, 150 undergraduates were selected. Averagely, 40.74 Â± 14.39 hours per week was spent using electronic media for leisure and entertainment. Results showed that males with a high e-media user rate for entertainment or leisure had a generally low BMI mean while females with a high e-media user rate for entertainment or leisure had a higher BMI mean. Although exercise rate is better in general among male high e-media users, its effect is opposite among female high e-media users. As a possible strength, the involvement of multidisciplinary innovations is recommended in the use of social marketing programmes with a blend of social capital theory for e-media products and programmes.